Measuring staff training and development as a tool for high employees performance in Institut Pendidikan Guru Kampus Perempuan Melayu, Melaka / Shazwani Athirah Shaharuddin - Shaharuddin, Shazwani Athirah (Faculty of Business and Management, 2018)
All organizations would have the same objective which is to achieve standard of performance of their employees because it will help the organization to grow and success. Training and development one of the program designed to help the employees learn a new knowledge and skills to improve themselves. Effective training program will become one of the best way in order to increase employees’ performance.